Degree of nematode resistance in sweet potato cultivar 'mafutha' to tropical meloidogyne species - Nkosi, Simangele Princess (My University, 2019)
Most sweet potato-producing regions in South Africa are heavily infested by the root knot (Meloidogyne species) nematodes, which are difficult to manage since the withdrawal of the highly effective fumigant synthetic chemical nematicides. Prior to the withdrawal, the management of Meloidogyne species was not a priority in sweet potato (Ipomoea batatas L.) production since methyl bromide was highly effective in suppressing nematodes. The withdrawal resulted in the introduction of various alternative nematode management strategies, with nematode resistance being the most preferred. However, progress in the use of nematode resistance had been hindered by limited information on accurate species identification since Meloidogyne species have a wide host range and some biological races. The objectives of the study were (1) to determine the degree of nematode resistance in sweet potato cv. 'Mafutha' to M. javanica, M. incognita races 2 and M. incognita race 4 and (2) to investigate the mechanism of resistance in sweet potato cv. 'Mafutha' to M. javanica, M. incognita race 2 and M. incognita race 4. A total of six Experiments were conducted. In each, treatments comprised 0, 25, 50, 125, 250, 625, 1250, 3125 and 5250 eggs and second-stage juveniles (J2), arranged in a randomised complete block design (RCBD), with six replications. Uniform rooted sweet potato cuttings were transplanted in 20-cm-diameter plastic pots filled with steam pasteurised (300˚C for 1 hour) loam soil and Hygromix-T mixed at 3:1 (v/v) ratio. At 56 days after inoculation, plant variables and nematodes in roots were collected. Meloidogyne javanica inoculum levels in Experiment 1 had highly significant (P ≤ 0.01) effects on dry shoot mass and, stem diameter, contributing 74% and 50% in total treatment variation (TTV) of the respective variables, whereas under M. incognita race 2 inoculum levels contributed 70% and 56% in TTV of dry root mass and dry shoot mass, respectively. Meloidogyne incognita race 4 inoculum levels contributed 65% xx and 58% in TTV of stem diameter and dry shoot mass, respectively. In Experiment 2, M. javanica treatment levels contributed 56% in TTV of dry root mass, whereas M. incognita race 2 inoculum levels had no significant effect on any plant variable. In contrast, M. incognita race 4 contributed 51% in TTV of vine length. In Experiment 1, the nematode levels had significant effects on reproductive potential (RP) values, with treatments contributing 96%, 86% and 76% in TTV of RP values in M. javanica, M. incognita race 2 and M. incognita race 4, respectively. In Experiment 2, treatments contributed 79%, 46% and 61% in TTV of RP values in the respective Meloidogyne species. Results of the study suggested that growth of sweet potato cv. 'Mafutha' was affected by nematode infection, whereas the test nematodes were able to reproduce and develop on the test potato cultivar. In conclusion, sweet potato cv. 'Mafutha' was susceptible to M. javanica, M. incognita race 2 and M. incognita race 4 and therefore, the cultivar should not be included in crop rotation programmes intended to manage tropical Meloidogyne species and races in Limpopo Province, South Africa. Since the cultivar was susceptible to the test nematodes, the study did not evaluate the mechanism of resistance.
Thesis (M.Sc. Agriculture (Agronomy) -- University of Limpopo, 2019
Keywords: Sweet potato; Root knot (Meloidogyne species) nematodes; Root-knot; Nematode diseases of plants; Root-knot nematodes